(untitled) (Journal of the College of Basic Education, 2022)
The work of the novelist in the structure of the television drama series constituted a clear epistemological detail and a semantic transformation expressing the various patterns of narration and narration in the structure of the novel, which were embodied in the rhetoric of the image and its language through the movement of the camera and its significant transitions expressing the mechanism of juxtaposition between the two sexes, which was embodied in the expression of political, economic and historical events. social, cultural and ideological.